Three-dimensional radiative transfer - Tom Abel (Revista Mexicana de Astronomía y Astrofísica, 2000)
Radiative Transfer (RT) e ects play a crucial role in the thermal historyof the intergalactic medium. Here I discuss recent advances in the developmentof numerical methods that introduce RT to cosmological hydrodynamics. Thesemethods can also readily be applied to time dependent problems on interstellar andgalactic scales.